Hydrated ionic polymer for thermochromic smart windows in buildings - Huaiyuan Wang; Yuanwei Lu; Jie Wang; Tao Qi; Xuefeng Tian; Chaowei Yang; Yuming Huang; Meiqi Wang; Baiqi Zhang; Zhibin Qu; Wei Zhou; Fei Sun; et al. (Nature Communications)
Abstract Thermochromic smart windows offer an efficient solution to reduce building energy consumption by regulating solar radiation without external energy input. However, conventional thermochromic windows often struggle to achieve high luminous transmittance (>70%), strong solar modulation, and an optimal transition temperature (30–40 °C) simultaneously. Here, we present a hydrated ionic polymer thermochromic smart window, which transitions between transparent and blue states through temperature-induced hydration and dehydration. Notably, the smart windows exhibit significant solar modulation (ΔT sol = 30.5%) and high luminous transmittance (T lum = 87.7%), with an adjustable transition temperature range from 25 °C to 42 °C. Additionally, no significant performance degradation was observed after 200 heating-cooling cycles and 120 days under high-humidity conditions. Field tests showed that the smart windows can reduce indoor temperatures by up to 10 °C compared to clear windows. Simulations indicate a most probable energy-saving efficiency of 11.4% compared to clear windows, with further improvements up to 17.7% when combined with Low-E glass in warm climates. This work delivers a high-performance thermochromic smart window and offers a promising strategy for improving building energy efficiency and promoting global sustainability.